Design of a high performance AC-DC LED driver based on SEPIC topology - Fouzia Ferdous; A. B. M. Harun ur Rashid (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Light emitting diodes (LEDs) are current driven devices. So, it is essential to maintain the stability of LED voltage and current. Variation of temperature may cause of instabilities and bifurcations in the LED driver. Driving LEDs from an offline power source faces design challenges like it have to maintain low harmonics in input current, to achieve high power factor, high efficiency and to maintain constant LED current and to ensure long lifetime. This paper proposes the technique of harmonics reduction by using parametric optimization of Single ended primary inductor converter (SEPIC) based LED driver. Without optimization of SEPIC parameters input energy will not be properly transferred to the load and this un-transferred energy will be transmitted to the source. Consequently, the quality of input current will be hampered i.e. harmonics will contaminate the input current. Focussing this, the paper has presented the design of a non-isolated integrated-stage single-switch constant current LED driver operating in discontinuous conduction mode (DCM) in SEPIC incorporating the design of control circuit with soft start mechanism. This LED driver has achieved a good efficiency (90.6%) and high-power factor (0.98) with reduced harmonics (3.35%). System stability has been determined and simulation studies are performed to confirm the validity of the LED driver circuit. A laboratory prototype is built.